Families, families, families! - Lang, Suzanne; Lang, Max, 1982- (New York : Random House, 2015)
"A host of animals portrays all kinds of non-traditional families"--Provided by publisher.
School Library Journal, December 2014.
1.7.
K-3.
Keywords: Families -- Juvenile fiction; Animals -- Juvenile fiction; Families -- Fiction; Animals -- Fiction; Stories in rhyme; Family life -- Fiction; Animals -- Fiction; Stories in rhyme; Stories in rhyme; Families -- Fiction; Animals -- Fiction; Picture books for children